SHARIA FINANCIAL MANAGEMENT IN PESANTREN-OWNED ENTERPRISES (BUMPES) IN EAST JAVA - Cici Rosmala; Satria Berbudi; Ari Sarah Sofura; Devika Rosa Guspita (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine sharia financial management practices in BUMPes and their implications for the institutional and economic sustainability of Islamic boarding schools. The research was conducted across five Islamic boarding schools in East Java, namely Al-Hasan (Ponorogo), Al-Muttaqien (Ponorogo), Al-Huda (Madiun), Al-Thohiriyah (Magetan), and Darul Ulum (Poncol). A qualitative multi-site research design was employed. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using data condensation, data display, and conclusion drawing through both within-site and cross-site analyses. The findings indicate that sharia financial management in BUMPes is grounded in the principles of trustworthiness, honesty, justice, and transparency. However, its implementation remains largely normative and has not yet been fully institutionalized within a professional governance framework. Cross-site analysis reveals that Islamic boarding schools characterized by more structured governance systems, stronger accountability mechanisms, and greater managerial capacity demonstrate higher levels of institutional and economic performance. Key supporting factors include a strong religious culture, leadership commitment, and an established internal customer base. Conversely, major constraints include limited human resource capacity, weak financial administration, the absence of standardized sharia operating procedures, and low levels of digitalization. Based on the synthesis of cross-site findings, this study proposes an Integrated Sharia Financial Management Model for Islamic Boarding School Institutions that incorporates Islamic values, governance mechanisms, human resource development, and business innovation. The model contributes to the literature on sharia financial governance within pesantren-based institutions and offers a practical framework for enhancing the professionalism, accountability, and long-term sustainability of BUMPes.